Effect of Electrolyte Composition on Performance and Stability of Lithium–Sulfur Batteries. Issue 12 (27th May 2019) - Ishino, Yuki; Takahashi, Keitaro; Murata, Wataru; Umebayashi, Yasuhiro; Tsuzuki, Seiji; Watanabe, Masayoshi; Kamaya, Minori; Seki, Shiro
Abstract : The development of new electrolytes for lithium–sulfur (Li–S) batteries is important. Electrolytes based on 1:1 glyme:Li + complexes can be locally destroyed to form free glyme during charge/discharge cycles. Free glyme can cause Li2 S x dissolution, which is a major factor in Li–S battery degradation. To decrease the local generation of free glyme, the glyme:Li + electrolytes with higher proportions of Li salts are developed to control the Li2 S x dissolution into the electrolyte. The chemical solubility of Li2 S8 and the charge/discharge properties of Li–S cells are investigated by varying the glyme:Li salt molar ratio. Nonequimolar (high Li salt concentration) glyme:Li salt mixture electrolytes directly suppress the Li2 S8 dissolution and improve the charge/discharge properties (cycling and coulombic efficiency) of Li–S cells. The electrolyte composition can control the chemical stability of reactive intermediates at the Li2 S x electrode and provide high‐performance Li–S cells for next‐generation batteries. Abstract : Simple electrolyte composition controls the chemical stability of the reactive intermediate of the Li2 S x electrode and leads to high‐performance of Li–S cells for next‐generation batteries.